Lower-bound complexity algorithm for task scheduling on heterogeneous grid - Atef, Asmaa; Hagras, Tarek; Mahdy, Yousef B.; Janeček, Jan (Computing, 2017)
The problem of best schedule of dependent-tasks application into nodes of computational grid in low complexity is the most important issue to obtain high performance application execution. Scheduling can be performed at compile-time or at run-time depends on tasks and grid-nodes available information. Due to the NP-completeness of the problem, heuristics are used in compile-time solution of the problem. Two of these heuristics are list-scheduling and duplication-based. List-scheduling heuristics produce reasonable schedule in reasonable time complexity, while duplication-based heuristics produce better schedule in higher time complexity. Many algorithms based on list-scheduling and duplication-based heuristics have been addressed in the literature. This paper proposes a scheduling algorithm based on list-scheduling and duplication-based heuristics. The algorithm is called Best-Node based Critical-Parent. The algorithm keeps the lower-bound complexity of any classes of heuristics-based scheduling algorithms. Random generated applications, in addition to real-world applications have been examined. The experimental results based on computer simulation show that the proposed algorithm performed better than the most-recent and well-known existing algorithms.